Pengaruh Likuiditas dan Solvabilitas Melalui Profitabilitas terhadap Nilai Perusahaan - Ali Akbar (Universitas Batanghari Jambi, 2021)
The purpose of this research is to know and analyze the influence of liquidity and solvency through profitability on the corporate value at pharmaceutical sub-sector companies in the Indonesia stock exchange. That research is using data of secondary from annual financial statements and closing stock prices. sample in the research are pharmaceutical sub-sector companies in the Indonesia stock exchange period 2015-2019. With the purposive sampling method used there are nine companies that are sampled in this research. Data analysis in this research uses path analysis with SPSS software. The resulting research informs :1) simultaneously the current ratio and debt to asset ratio variables have significant effect on the return on asset variable, 2) the current ratio variable partially has positive and significant effect on the return on asset variable, 3) the debt to asset ratio variable partially has negative and insignificant effect on the return on asset variable, 4) the current ratio and debt to asset ratio variables simultaneously have significant effect on the stock price variable, 5) partially current ratio and debt to asset ratio variable have positive and significant effect on the stock price variable, 6) return on asset variable has positive and significant effect on the stock price variable, 7) indirectly current ratio and debt to ratio variables return on asset through variable have insignificant effect on the stock price variable.